ҚАРАҚАЛПАҚ ТИЛИНДЕ «ҚАР» СОМАТИЗМИНИҢ СЕМАНТИКАЛЫҚ БИЛДИРИЛИЎИ - Шынназарова, С.Ж. (FAN va JAMIYAT, 2025)
The article discusses the somatism “Qar” in the Karakalpak language. The semantic field of the somatism “Qar” is substantiated with examples drawn from literary works. The specific semantics of the somatism “qar” in the Karakalpak language has been analyzed.